If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 + -3(2k + 4) = -8 Reorder the terms: -6 + -3(4 + 2k) = -8 -6 + (4 * -3 + 2k * -3) = -8 -6 + (-12 + -6k) = -8 Combine like terms: -6 + -12 = -18 -18 + -6k = -8 Solving -18 + -6k = -8 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + -6k = -8 + 18 Combine like terms: -18 + 18 = 0 0 + -6k = -8 + 18 -6k = -8 + 18 Combine like terms: -8 + 18 = 10 -6k = 10 Divide each side by '-6'. k = -1.666666667 Simplifying k = -1.666666667
| 4(2x-3)=-5 | | 3x(2x-3)=0 | | 6x^2+4x-54=0 | | 4x+6x=10x | | p+p+p+p= | | 19=3x | | X(4X+5)-3=0 | | X(4X+5)-3=5 | | 4(-4t^2+27-45)=0 | | 5x-3=-1 | | 9x^2+60x+100=0 | | 6(3-a)+7(3a+2)-4(a+5)= | | 9x-5x+8x-6x= | | (2+y)+y=4 | | 15-13x-20x^2=0 | | -X+2y=1 | | 5+(2-3)-(6-4)+7= | | 2x-10=48 | | 14+(-3)-(-6)+8= | | 7(2)+7y=-10 | | 72+7y=-10 | | X+(2+X)=4 | | 54+68=158 | | 6(k-2)-7=3k-(2k-3) | | 6w^2-4w^3= | | 1/2(6x+4)=x+2(x+1) | | 2(x+1)=8-x | | 4a-5=2(a+1)+9a+2 | | x-6=2(x-5)-6(x-4) | | 21.00+0.50x-0.50x=1.50x-0.50x | | 4y=-40 | | x^2+50x+47=0 |